2014
DOI: 10.2298/sarh1406325m
|View full text |Cite
|
Sign up to set email alerts
|

Early clinical results of surgical treatment of patients with femoroacetabular impingement

Abstract: Postoperative results have shown that the surgical approach to treating patients with femoroacetabular impingement is the method of choice. Three operated patients, with advanced osteoarthritis of the hip, had to be converted to total hip replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…These studies all reported significant correction from pre operative alpha angles. The pooled mean femoral head-neck offset reported post-operatively was 10.3 ± 2.58 mm (range 6.0-18.1 mm) across four studies [10,34,40,41], while Graves and Mast [39] did not report discrete values but stated that the offset returned to normal. Mean head-neck offset ratio was reported in two studies to be 0.21 [32] and 0.17 [41] postoperatively.…”
Section: Cam-type Faimentioning
confidence: 95%
See 3 more Smart Citations
“…These studies all reported significant correction from pre operative alpha angles. The pooled mean femoral head-neck offset reported post-operatively was 10.3 ± 2.58 mm (range 6.0-18.1 mm) across four studies [10,34,40,41], while Graves and Mast [39] did not report discrete values but stated that the offset returned to normal. Mean head-neck offset ratio was reported in two studies to be 0.21 [32] and 0.17 [41] postoperatively.…”
Section: Cam-type Faimentioning
confidence: 95%
“…Three studies compared arthroscopic management with open surgical FAI treatment [34][35][36], while one study compared open surgical correction with a control group of normal radiographs [37]. The remaining studies reported either arthroscopic combined with open surgical approaches [9][10][11] or open surgical procedures only [13,32,33,[38][39][40][41][42][43][44][45]. Table 1 lists descriptive characteristics of the studies included for analysis.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Femoroacetabular impingement (FAI) is the cause of the hip pain in young adults and is a potential cause of a hip arthrosis development [1][2][3][4][5][6][7][8][9] . The minimal bone changes of the proximal femur and/or acetabulum combined with FAI as a pathophysiological mechanism, lead to an early labrum lesion and adjacent cartilage.…”
Section: Introductionmentioning
confidence: 99%